A comparison of biomarkers in assessing the combined effects of pesticide mixtures on non-target soil invertebrates - Gola, Nontuthuzelo Pearl (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004.